Problems in Implementing Competency-Based Programs - Huff, Sheila; Syracuse Univ. Research Corp., NY. Educational Policy Research Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The problems confronting educators attempting to develop and implement competency based education (CBE) programs at the secondary and post secondary levels are indeed challenging. There is no uniformity with regard to key elements in competency based programs, such as educational goals, curriculum, institutional environment, pedagogical techniques, evaluation of student performance, and rules and procedures. This lack of uniformity makes definition of competency based education difficult. The author outlines some of the problems arising in the implementation of competency based programs in 24 areas, including staff recruitment, development, and evaluation, budgeting, credentialing, community relations, relations with parents, research and information acquisition, program evaluation, legal questions, organizational sturcture, and student admissions and advising. She concludes that considerable educational innovation is occurring under the rubric of CBE and calls for more assistance from the research and development community for harried educators. (Author/DS)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: 400-75-0036.
ERIC Note: Not available in paper copy due to marginal legibility of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competency Based Education; Competency Based Teacher Education; Educational Development; Educational Innovation; Educational Objectives; Educational Problems; Educational Programs; Postsecondary Education; Program Development; Secondary Education; Teachers